2004
DOI: 10.1074/jbc.m404184200
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Role of Aspartate in a Short Strong Hydrogen Bond of the Asp274–His32 Catalytic Dyad in Phosphatidylinositol-specific Phospholipase C Can Be Substituted by a Chloride Ion

Abstract: Phosphatidylinositol-specific phospholipase C from Bacillus thuringiensis catalyzes the cleavage of the phosphorus-oxygen bond in phosphatidylinositol. The focus of this work is to dissect the roles of the carboxylate side chain of Asp 274 in the Asp 274 -His 32 dyad, where a short strong hydrogen bond (SSHB) was shown to exist based on NMR criteria. A regular hydrogen bond (HB) was observed in D274N, and no low field proton resonance was detected for D274E and D274A. Comparison of the activity of wild type, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…In addition, the catalytic activities of the Y30F/Y55F and Y30F/Y55F/Y115F KSIs were only slightly decreased compared with that of the wild-type enzyme in spite of the conversion of LBHB to an ordinary hydrogen bond in these mutant KSIs. Similar observations have also been reported in other enzyme systems ( Stratton et al, 2001 ; Zhao et al, 2004 ). A serine protease, subtilisin BPN’ demonstrated a downfield NMR resonance near 18 ppm that was considered to originate from LBHB in the wild-type subtilisin ( Stratton et al, 2001 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the catalytic activities of the Y30F/Y55F and Y30F/Y55F/Y115F KSIs were only slightly decreased compared with that of the wild-type enzyme in spite of the conversion of LBHB to an ordinary hydrogen bond in these mutant KSIs. Similar observations have also been reported in other enzyme systems ( Stratton et al, 2001 ; Zhao et al, 2004 ). A serine protease, subtilisin BPN’ demonstrated a downfield NMR resonance near 18 ppm that was considered to originate from LBHB in the wild-type subtilisin ( Stratton et al, 2001 ).…”
Section: Discussionsupporting
confidence: 91%
“…The kinase (proteintyrosine kinase C-terminal Src kinase) has an active site that pairs an aspartate with a nearby arginine (four residues away) and looks remarkably like the active site of Pus1p. Earlier work had shown that chemical rescue of a mutant enzyme, that replaces the arginine with alanine, was possible and that the class of small molecules that might restore activity could be predicted given knowledge of the composition of the active site (Williams et al 2000;Zhao et al 2004a). By understanding the topography of the active site of hPus1p and determining the flexibility of the requirements for particular amino acids that compose it, the pathway to identifying a class of compounds that could be considered for recovery of mutant hPus1p activity might be less uncertain.…”
Section: Modification Of Uridine At Position 30mentioning
confidence: 99%
“…On the other hand, typical CA activity is achieved by the capture of a proton from a water molecule that is located at the fourth coordination position of zinc, and the released hydroxide attacks the nearby carbon dioxide to form bicarbonate (HewettEmmett and Tashian, 1996). It seems that the His95-Asp70 interaction of dioscorin ( Figure 1D) can initiate the processes of both DHA reduction and proton capture of CA activity with the assistance of water molecules, and the His-Asp catalytic dyad was also identified in ribonuclease A, phospholipase C and phospholipase A2 (Quirk and Raines, 1999;Zhao et al, 2004;Murakami and Lambeau, 2013). In addition, the Asp70 and His95 residues are conserved in all dioscorins registered in the NCBI protein database and Asp70 is not found in a-CAs (Supplemental Figures 3 and 4 and Shewry, 2003).…”
Section: Molecular Plantmentioning
confidence: 97%
“…The putative mechanism of DHA reduction by dioscorin is shown in Figure 1G. First, Asp70 forms a hydrogen bond with His95 (left top), and the resulting complex serves as a general base catalyst (Zhao et al, 2004). One proton is taken from a water molecule nearby (left middle) and passed to the O3 atom of the DHA molecule, where it enters the active site of dioscorin (left bottom).…”
Section: Molecular Plantmentioning
confidence: 99%